2001
DOI: 10.1086/321910
|View full text |Cite
|
Sign up to set email alerts
|

Endocarditis Caused by Penicillin‐Resistant Viridans Streptococci: 2 Cases and Controversies in Therapy

Abstract: Although penicillin-resistant viridans streptococci have been isolated from samples from the mouth, blood, and wounds in increasing numbers, viridans streptococci isolated from patients with endocarditis have remained sensitive to penicillin for the past 5 decades. We report the cases of 2 patients with penicillin-resistant viridans streptococcal endocarditis, review 6 other cases from the literature, and summarize 2 studies that used an animal model of penicillin-resistant viridans streptococcal endocarditis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 9 publications
0
19
0
1
Order By: Relevance
“…VGS and Streptococcus bovis cause almost one-quarter of all cases of infective endocarditis (IE) (3). Beta-lactams are the drugs of choice; however, penicillin-resistant strains are increasingly being isolated in Europe and the United States and have become a matter for concern (4-6), since their management is challenging (7). Vancomycin is the recommended antibiotic for endocarditis in cases of resistance to penicillin or allergy to beta-lactams (8)(9)(10).…”
mentioning
confidence: 99%
“…VGS and Streptococcus bovis cause almost one-quarter of all cases of infective endocarditis (IE) (3). Beta-lactams are the drugs of choice; however, penicillin-resistant strains are increasingly being isolated in Europe and the United States and have become a matter for concern (4-6), since their management is challenging (7). Vancomycin is the recommended antibiotic for endocarditis in cases of resistance to penicillin or allergy to beta-lactams (8)(9)(10).…”
mentioning
confidence: 99%
“…Several studies also indicated that full expression of resistance necessitates mutations both in the pbp genes and in other genes, of which only a few have been determined, namely, in the ciaRH, cpoA, and murMN loci (8,9,14). The same mechanism has also been found in viridians streptococci, which are occasionally responsible for human infections (18,26). Very recent reports also demonstrated the implication of PBP mutations in S. agalactiae presenting a decreased susceptibility to penicillin (4, 17, 21).…”
mentioning
confidence: 99%
“…occasionally responsible for infections (21,24,34). In these microbes, modifications of the penicillin-binding proteins (PBPs) leading to a decreased affinity for the drug are at the forefront of the resistance mechanism.…”
mentioning
confidence: 99%